2023
DOI: 10.3389/fimmu.2023.1110843
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of Mycobacterium tuberculosis DNA vaccines on the mouse model with latent tuberculosis infection

Abstract: BackgroundAbout a quarter of the world’s population with latent tuberculosis infection (LTBI) are the main source of active tuberculosis. Bacillus Calmette Guerin (BCG) cannot effectively control LTBI individuals from developing diseases. Latency-related antigens can induce T lymphocytes of LTBI individuals to produce higher IFN-γ levels than tuberculosis patients and normal subjects. Herein, we firstly compared the effects of M. tuberculosis (MTB) ag85ab and 7 latent DNA vaccines on clearing latent MTB and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Reece et al engineered therv3407 gene into the BCG vaccine and immunized mice with the recombinant BCG vaccine, and found that this modified BCG vaccine stimulated high levels of IFN-γ production in mice and markedly enhanced protection against TB (30). Our research group also found through animal experiments that the mice immunized with the rv3407 DNA vaccine could produce higher levels of antigen-specific IFN-γ in the culture supernatant of splenic lymphocytes, had more Th1 cells and an increased Th1/Th2 cells ratio in the whole blood, could reduce the bacterial load in the lungs of mouse models with acute infection or LTBI, and alleviate the degree of lung lesions (31,32).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Reece et al engineered therv3407 gene into the BCG vaccine and immunized mice with the recombinant BCG vaccine, and found that this modified BCG vaccine stimulated high levels of IFN-γ production in mice and markedly enhanced protection against TB (30). Our research group also found through animal experiments that the mice immunized with the rv3407 DNA vaccine could produce higher levels of antigen-specific IFN-γ in the culture supernatant of splenic lymphocytes, had more Th1 cells and an increased Th1/Th2 cells ratio in the whole blood, could reduce the bacterial load in the lungs of mouse models with acute infection or LTBI, and alleviate the degree of lung lesions (31,32).…”
Section: Introductionmentioning
confidence: 77%
“…Mice were divided into three groups (8 mice per group) and treated as follows: 1) Control group: each mouse was injected intramuscularly with 100 μl of saline; 2) pVAX1 group: each mouse was injected intramuscularly with 100 μg pVAX1 plasmid diluted in 100 μl saline; 3) Vaccine group: each mouse was injected intramuscularly with 100 μg W541 DNA vaccine diluted in 100 μl saline (32). Mice received injections every two weeks for a total of 3 injections.…”
Section: Immunization Of the Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, clinical studies have demonstrated that using Vaccae™ as an adjunctive immunotherapy, significantly enhances the sputum smear negative conversion rate (68%), facilitates lesion improvement, and cavity closure, shortens treatment duration, and mitigates chemotherapy-related damage ( Bourinbaiar et al., 2020 ; Yang et al., 2011 ). As a prophylactic vaccine, Vaccae™ can effectively suppress the proliferation and activation of Mtb , hinder the progression of LTBI, and decrease the rate of infection ( Liang et al., 2023 ; Sun ZhaoPing et al., 2013 ).…”
Section: Whole-cell Bacterial Vaccinesmentioning
confidence: 99%
“…Liang et al employed a drug‐activated mouse LTBI animal model to evaluate the protective effects of a DNA vaccine constructed with Mtb ag85ab and seven latency‐associated antigens (rv1733c, rv2660c, rv1813c, rv2029c, rv2628, rv2659c, rv3407). They found that antigens rv2659c and rv1733c could significantly enhance the protective efficacy in LTBI mice (Liang et al, 2023).…”
Section: Vaccine Development Focus On Ltbimentioning
confidence: 99%